A study of a complex of bioactive compounds in the fruits of promising blue honeysuckle (Lonicera caerulea L.) cultivars - I. B. Perova; K. I. Eller; M. A. Gerasimov; V. A. Baturina; M. Yu. Akimov; O. M. Akimova; A. M. Mironov; V. A. Koltsov (Труды по прикладной ботанике, генетике и селекции)
Background. Blue honeysuckle (Lonicera caerulea L.) is a valuable source of bioactive compounds (BAC) of polyphenolic nature and rare for horticultural berries iridoids, which have antioxidant, anti-inflammatory, antimicrobial and other properties and are widely used in the food, medical and cosmetic industries.Materials and methods. The berries of 20 released honeysuckle cultivars of Russian, Canadian and U.S. origin, reproduced at the I.V. Michurin Federal Science Center in Tambov Province, were studied for the content of the main BAC groups using modern methods (spectrophotometry, HPLC-UV, HPLC-RID, and HPLC-DAD-MS).Results and discussion. The main BAC groups (the content and profile of anthocyanins, proanthocyanidins, flavonols and flavones, hydroxycinnamic acids (HCA), iridoids, and organic acids) as well as mono- and disaccharides were studied in detail. A comparative study of the biological value of domestic and foreign honeysuckle cultivars was carried out.Conclusions. The study resulted in identifying the most promising cultivars of honeysuckle according to the content of the main BAC groups.